Impact analysis of traction loads on power grid based on probabilistic three‐phases load flow. Issue 16 (19th December 2018) - Che, Yulong; Wang, Xiaoru; Lv, Xiaoqin; Hu, Yi; Li, Longyuan; Chen, Haoyue
Abstract : Electrified railway traction power supply system is directly powered by 110 kV or 220 kV (some 330 kV) high‐voltage power grid. The uncertainty, non‐linearity, and asymmetry of traction loads like the electric locomotives and electric multiple units (EMUs) exert the negative sequence and harmonics impact on the high‐voltage transmission network. In order to evaluate the impact of the uncertainty and asymmetry of traction loads on the high‐voltage transmission grid, a probabilistic three‐phase power flow model of transmission network considering the probability model of traction loads is proposed. First, the power probability model of traction loads is established according to the running characteristics of traction loads. Second, the Monte Carlo simulation method is applied for the probabilistic three‐phase power flow model calculation considering the traction loads. Finally, the simulation calculation is carried out on the balanced IEEE‐14 bus three‐phase test system. The results show that the asymmetric traction loads cause the unbalance of the grid nearby to deteriorate. The further away from the traction substation, the smaller impact of the traction loads.